2024
DOI: 10.1037/amp0001218
|View full text |Cite
|
Sign up to set email alerts
|

Increased functional connectivity between the midbrain and frontal cortex following bright light therapy in subthreshold depression: A randomized clinical trial.

Guanmao Chen,
Pan Chen,
Zibin Yang
et al.

Abstract: The underlying mechanisms of bright light therapy (BLT) in the prevention of individuals with subthreshold depression symptoms are yet to be elucidated. The goal of the study was to assess the correlation between midbrain monoamine-producing nuclei treatment-related functional connectivity (FC) changes and depressive symptom improvements in subthreshold depression. This double-blind, randomized, placebo-controlled clinical trial was conducted between March 2020 and June 2022. A total of 74 young adults with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…Lastly, the study published by Elias and colleagues (2022) revealed that RSFC between the whole habenula and the dlPFC was higher when DBS of the SCC was turned on compared to when it was turned off. Overall, three studies could be interpreted as indicating that depression is associated with increased RSFC between the dlPFC and the habenula (Chen et al, 2023;Mao et al, 2023;Wu et al, 2020). One study found no difference in RSFC between the whole habenula 5 and the dlPFC between MDD and HCs (Yang, Jin et al, 2022), while the results of the last study do not inform us in this regard (Elias et al, 2022).…”
Section: Other Regionsmentioning
confidence: 94%
See 1 more Smart Citation
“…Lastly, the study published by Elias and colleagues (2022) revealed that RSFC between the whole habenula and the dlPFC was higher when DBS of the SCC was turned on compared to when it was turned off. Overall, three studies could be interpreted as indicating that depression is associated with increased RSFC between the dlPFC and the habenula (Chen et al, 2023;Mao et al, 2023;Wu et al, 2020). One study found no difference in RSFC between the whole habenula 5 and the dlPFC between MDD and HCs (Yang, Jin et al, 2022), while the results of the last study do not inform us in this regard (Elias et al, 2022).…”
Section: Other Regionsmentioning
confidence: 94%
“…These two studies nevertheless reported correlations between depressive symptoms and the resting-state functional connectivity (RSFC) of the habenula. Of the 22 studies directly interested in mood disorders, 16 conducted analyses comparing the connectivity of the habenula between groups, and six investigated how the connectivity of the habenula changes in response to depression treatments: ketamine injections (Chen et al, 2024;Rivas-Grajales et al, 2021;Wang, Chen et al, 2022), bright light therapy (Chen et al, 2023), DBS (Elias et al, 2022), and electroconvulsive therapy (ECT) (Gao et al, 2021). From these same 22 studies, 15 conducted a seed-to-whole-brain analysis with the habenula as a seed.…”
Section: Connectivity Studiesmentioning
confidence: 99%
“…To evaluate the effect of BLT on the improvement of clinical symptoms and cognitive functions of StD and on the cerebellar sFC and dFC based on randomized controlled trials, StD participants were randomly allocated to BLT group and the placebo group with randomization codes. The BLT group was treated with 5000 lux for 8 weeks, and placebo group was treated with an inactive device (emitting weak light < 5 lux) for 8 weeks ( Chen et al, 2023 ; Jiang et al, 2020 ). Clinical symptoms and cognitive functions were assessed at baseline and 8 weeks after treatment, and structural and functional MRI data were also collected.…”
Section: Methodsmentioning
confidence: 99%
“…BLT has been proven to have the same therapeutic effect as antidepressants and is well tolerated in the treatment by patients ( Jiang et al, 2020 ; Lam et al, 2016 ). Previous work of our team found that BLT was effective in relieving depressive and anxiety symptoms in individuals with StD by increasing the functional connectivity (FC) between the midbrain and frontal cortex ( Chen et al, 2023 ; Jiang et al, 2020 ). In addition, the effects of light therapy go beyond mood improvement to improve cognition functions ( Huang, Tao & Ren, 2023 ; Riemersma-van der Lek et al, 2008 ), including alertness ( Mu et al, 2022 ; Pachito et al, 2018 ), attention ( Liu, Liou & Jou, 2021 ), memory ( Huang et al, 2021 ), and executive function ( Killgore, Vanuk, Shane, Weber & Bajaj, 2020 ) as well.…”
Section: Introductionmentioning
confidence: 98%